University Language Policies in an Era of Internationalisation: An Analysis of Language of Publishing Shift at a South African University - Mwaniki, Munene (South African Journal of Higher Education, 2016)
The research reported in this article sought to interrogate the impact of internationalisation on university language policies with a focus on how pressures of internationalisation influence the publication practices and choices of language of publishing by researchers at the University of the Free State, South Africa. The research uses the theoretical framework of linguistic culture and its dyad of overt versus covert language policies. The research analysed policy documents and research output data from 2000 to 2008. The results indicate that despite the university’s articulated overt trilingual language policy, the pressures of internationalisation have led the university to adopt other policies which constitute a covert language policy, which is leading to a significant shift in language of publication by UFS researchers. Analysis of research output data indicates a mean annual shift of 1.34% towards English as the preferred language of publication at the UFS. The results point to a near complete shift to English as the preferred language of publication by researchers in the university by 2018. This development indicates that in an era of internationalisation, university language policies are but a small component of the macro dynamic that determines language choice(s) within universities.